ÙØ¹Ø§Ù„ÙŠØ© Ø·Ø±ÙŠÙ‚Ø© Ø±Ø³Ù… Ø§Ù„Ø®Ø±Ø§Ø¦Ø· Ø§Ù„Ø°Ù‡Ù†ÙŠØ© Ù„ØªØ±Ù‚ÙŠØ© ÙÙ‡Ù… Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ù„Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù„ØºØ©Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - zahrotul Aini; Ariandi Ariandi (Lughatu Ad-Dhat, 2021)
This study aims to find out how the mind was effective or ineffective in increasing the ability of the Arabic language to the Indonesian language of the eighth grade students in the Integrated Islamic Intermediate School in the Civil Institute of Palangi. This research was conducted in the eighth semester of the Integrated Islamic Intermediate School in Madani Balangouqi. The population in this study is the eighth semester of the Integrated Islamic Intermediate School at the Civic Institute of Palnguqi. The model includes two semesters, the eighth chapter A as an experimental class and the eighth chapter B as an arbitration class. This research is quasi-experimental with the design of a pre- and post-test team control group. And the variables of this research are either the freedom variable based on the method of teaching mental mapping, or the linking variable to improve students' understanding of Arabic grammar. The hypothesis testing consists of two stages: The first stage using descriptive hypothesis testing techniques. And the second stage using the exam, which was pre-tested for tests of normality and homogeneity. The result showed that the method of studying mental mapping is effective in promoting the ability of students in the eighth semester in understanding the grammar of the Arabic language. Keywords: Mind Mapping Method, Grammar, Studying Arabic Â